Propagation graph fusion for multi-modal medical content-based retrieval - Sidong Liu; Siqi Liu; Pujol, Sonia; Kikinis, Ron; Dagan Feng; Weidong Cai (2014 13th International Conference on Control Automation Robotics & Vision (ICARCV), 2014)
Medical content-based retrieval (MCBR) plays an important role in computer aided diagnosis and clinical decision support. Multi-modal imaging data have been increasingly used in MCBR, as they could provide more insights of the diseases and complement the deficiencies of single-modal data. However, it is very challenging to fuse data in different modalities since they have different physical fundamentals and large value range variations. In this study, we propose a novel Propagation Graph Fusion (PGF) framework for multi-modal medical data retrieval. PGF models the subjects' relationships in single modalities using the directed propagation graphs, and then fuses the graphs into a single graph by summing up the edge weights. Our proposed PGF method could reduce the large inter-modality and inter-subject variations, and can be solved efficiently using the PageRank algorithm. We test the proposed method on a public medical database with 331 subjects using features extracted from two imaging modalities, PET and MRI. The preliminary results show that our PGF method could enhance multi-modal retrieval and modestly outperform the state-of-the-art single-modal and multi-modal retrieval methods.